The physiological profiles of Saudi elite judo athletes - Alahmadi, M. A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
One of the most highly physiologically demanding combat sports is Judo, which requires an excellent level of physical fitness in order to be successful in international competitions. Therefore, the aim of this study was to assess the physiological profiles of Saudi elite judo athletes. 14 judo athletes (mean ± SD, age, 17 ± 4 years; body mass, 66.7 ± 21 kg; height, 160.2 ± 13.6 cm) performed the Special Judo Fitness Test (SJFT) and a maximal multistage 20-m shuttle run test to estimate maximal oxygen consumption (VO2max). Body fat percentage (BF%) was determined by bioelectrical impedance scale. Hand grip strength was measured by hand grip dynamometer and flexibility was determined by using Sit-and-Reach Test. The mean (±SD) of the index of the SJFT and VO2max were 16.2 ± 1.6 and 42.5 ± 8.5 (ml/kgmin), respectively. The mean (±SD) of BF%, hand grip strength, and flexibility were 24.1±7.2 (%), 31.4±11.5 (kg), and 34.6±6.7 (cm), respectively. It is concluded that the SJFT was lower and BF% was higher in Saudi Judo athletes, compared to international elite Judo athletes